Visualization Experiment on the Pulsating Heat Pipe with Graphene Nanofluids - Ho, Ya-Chi; Fu, Chih-Yuan; Hu, En-Lan; Chang, Liang-Juan; Yao, Da-Jeng (Proceedings of the ... IEEE Conference on Nanotechnology, 2023)
This paper reports a graphene nanofluids-added pulsating heat pipe visualization study. Compared with the existing technology, graphene nanofluid can increase the bubble generation speed and the gas column push speed. Using visual experimental tests and high-speed cameras to observe the flow of air bubbles and air columns, it is found that the speed is 3-5 times higher than that of pure water, which improves heat exchange.